Increasing the efficiency of paired‐stimulus preference assessments by identifying categories of preference. Issue 1 (March 2015) - Ciccone, Francis J.; Graff, Richard B.; Ahearn, William H.
<x xml:space="preserve">Abstract</x> A paired‐stimulus preference assessment was conducted for 6 individuals with developmental disabilities. We selected stimuli that were representatives of 4 categories: chocolate, salty and crunchy, gummy, and fruit and vegetable. For all 6 participants, at least 3 of the 5 most preferred items came from the same category. On subsequent reinforcer assessments, items from the highest ranked preference category, some of which were included in the preference assessments and some of which were not, functioned as reinforcers. These findings suggest that after categories of preferred items are identified, clinicians may be able to identify reinforcers for some individuals without conducting additional assessments.